2005
DOI: 10.1007/s10803-005-5037-8
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Prenatal Stressors and Autism

Abstract: Recent evidence supports a role for genetics in autism, but other findings are difficult to reconcile with a purely genetic cause. Pathological changes in the cerebellum in autism are thought to correspond to an event before 30-32 weeks gestation. Our purpose was to determine whether there is an increased incidence of stressors in autism before this time period. Surveys regarding incidence and timing of prenatal stressors were distributed to specialized schools and clinics for autism and Down syndrome, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
230
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(261 citation statements)
references
References 39 publications
22
230
0
9
Order By: Relevance
“…As noted previously, autism risk factors include environmental challenges, such as maternal use of pharmaceutical agents with neurotoxic effects, [226][227][228]241,242 prenatal exposure to viral infections or maternal stress 233,234 and, in addition, exposure to high levels of environmental pollutants, including heavy metals. 275,276 A recent review by Herbert et al 7 identified 135 genes that have been shown to mediate responses to environmental challenge, and that are located within autism linkage regions.…”
Section: Genes Responsive To Environmental Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…As noted previously, autism risk factors include environmental challenges, such as maternal use of pharmaceutical agents with neurotoxic effects, [226][227][228]241,242 prenatal exposure to viral infections or maternal stress 233,234 and, in addition, exposure to high levels of environmental pollutants, including heavy metals. 275,276 A recent review by Herbert et al 7 identified 135 genes that have been shown to mediate responses to environmental challenge, and that are located within autism linkage regions.…”
Section: Genes Responsive To Environmental Factorsmentioning
confidence: 97%
“…232 In line with this premise, clinical surveys have linked complications during pregnancy, including viral infections and maternal stress, to a higher incidence of autism. 233,234 Other researchers have noted that autistic children have higher rates of physical malformations and facial dysmorphology, indicative of prenatal pathology. [235][236][237] These physical manifestations are predictive of greater symptom severity and neuroanatomical abnormalities.…”
Section: Mouse Models Of Environmental Contributions To Autism Etiologymentioning
confidence: 99%
“…This showed an incidence of 26.59/10,000 in the high exposure group, compared with that of 3.72/10,000 in the low exposure group. Beversdorf et al 46 also established a link between prenatal stress and autism. A number of other noteworthy fetal abnormalities have been linked with prenatal stress seen in the mother including cognitive, behavioural and emotional issues [47][48][49][50][51] .…”
Section: Behavioral and Psychological Problemsmentioning
confidence: 98%
“…Exposure to stress increases endogenous levels of catecholamines, which are ligands for the ADRB2, and autism has been associated with an increased number of reported stressful events occurring during 21-32 weeks gestation. 26 It was hypothesized that an association between ADRB2 genotype and autism would be greatest among pregnancies in which the mother had experienced relatively higher levels of stress. Evidence for 'sex-sensitive risk loci' 27 suggests that dichotomizing families according to whether they include an affected female will increase sample homogeneity with regard to the presence of malespecific versus female-specific risk loci.…”
Section: Introductionmentioning
confidence: 99%